Thermal and dielectric investigation of magnetic nanoparticles functionalized with PVC via click chemistry - Pekdemir, Mustafa Ersin; Tukur, Abdulrahman; Coskun, Mehmet (Springer, 2021)
In the first phase, PVC was modified with sodium azide through a nucleophilic substitution reaction. Then, the propargyl methacrylate was synthesized from propargyl alcohol and methacryloyl chloride. The copolymerization of propargyl methacrylate and vinyltrimethoxysilane was carried out by free-radical polymerization method in tetrahydrofuran (THF) at 70 degrees C in with AIBN as the initiator. The magnetic nanoparticle was bonded to vinyltrimethoxysilane units of the copolymer. Finally, the copolymer with propargyl end group bearing the magnetic nanoparticle on its side chain was bonded to PVC-N(3)by click reaction. FTIR spectroscopy was used for the characterization. The thermal stability of PVC decreased after the azidation reaction and increased by grafting of magnetic nanoparticles to the copolymer. Vibration sample magnetometer (VSM) measurements revealed that the product reached saturation magnetization (M-s) at 33.7 emu/g, while the pure Fe(3)O(4)nanoparticle showedM(s)value of 53.2 emu/g. As the applied frequency increased, the dielectric constant (epsilon ') and dielectric loss factor (epsilon '') of the copolymers diminished, while the AC conductivity (sigma(ac)) increased.
Keywords: PVC; Magnetic nanoparticle; Click chemistry; Thermal and dielectric